Estudio de factibilidad para el desarrollo de un sistema informático, que permita controlar las ventas y procesos administrativos de la Empresa Roberto, en la ciudad de Vinces - Taynys Zamora, Javier Armando (2021)
Through this study it is intended to demonstrate the feasibility of the implementation of a computer system in the company Roberto from the city of Vinces, which in the 21st century has been seen with a resistant stance towards technological change, even managing the methods little orthodox such as, for example, manually invoice the products sold, thus incurring errors such as the lack of control of your merchandise in the warehouse. It is necessary to emphasize the importance of the use of computer systems that allow automating and carrying out actions such as billing, so that it will allow timely decision-making when analyzing financial indicators. The research methodology used in this research was observation, to then place a study instrument known as an interview, which was carried out with the owner of this business under study. To finally analyze its feasibility and then analyze the conclusions left by this project